2016
DOI: 10.1093/database/bav096
|View full text |Cite|
|
Sign up to set email alerts
|

Ensembl comparative genomics resources

Abstract: Evolution provides the unifying framework with which to understand biology. The coherent investigation of genic and genomic data often requires comparative genomics analyses based on whole-genome alignments, sets of homologous genes and other relevant datasets in order to evaluate and answer evolutionary-related questions. However, the complexity and computational requirements of producing such data are substantial: this has led to only a small number of reference resources that are used for most comparative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
344
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(359 citation statements)
references
References 71 publications
(89 reference statements)
1
344
0
1
Order By: Relevance
“…Metagenomics allows the analysis of whole-genome sequences of DNA extracted from an organism, in which bioinformatic tools are used to individuate differences between the sequences [8]. It is an extremely powerful method that can be adopted to describe the genetic potential of several kinds of microbiome, and includes two fundamental approaches: the amplicon sequencing method, that uses the high-throughput 16S rRNA gene regions, and the shoutgun method which concerns the coverage of the genome outside of the small 16S rRNA gene region and this means that specific, strain level discrimination is achievable [9].…”
Section: Omics Sciencesmentioning
confidence: 99%
“…Metagenomics allows the analysis of whole-genome sequences of DNA extracted from an organism, in which bioinformatic tools are used to individuate differences between the sequences [8]. It is an extremely powerful method that can be adopted to describe the genetic potential of several kinds of microbiome, and includes two fundamental approaches: the amplicon sequencing method, that uses the high-throughput 16S rRNA gene regions, and the shoutgun method which concerns the coverage of the genome outside of the small 16S rRNA gene region and this means that specific, strain level discrimination is achievable [9].…”
Section: Omics Sciencesmentioning
confidence: 99%
“…Analysis of a gene gain/loss tree of 70 animal species through the Ensembl Compara utility [22,23] indicated that a single G6PC gene is present in the Drosophila genome, whereas lamprey (Petromyzon marinus, Cyclostomata) displays two genes and most bony fishes, birds, reptiles, amphibians and mammals have at least three paralogs. Possibly due to gene loss, no G6PC gene is described in the two Tunicata genomes included in the Ensembl Compara dataset.…”
Section: Evolutionary Origin Of the G6pc Gene Familymentioning
confidence: 99%
“…3,4 Genetic and genomic attributes have been studied in detail, and current knowledge is captured in databases, which include ENCODE, Ensembl, Gene, GEO and GWAS for humans, as well as other organism-specific examples. [5][6][7][8][9] The collated data are extensive and draw heavily both on state-of-the-art methods of gene sequencing and on extensive gene expression measurements, providing a basis for investigation of molecular evolution, disease-specific mutations and other. Despite this wealth of data, however, it is now clear that gene factors alone are insufficient to explain the complex mechanisms producing diversity and heritable changes in phenotype.…”
Section: Introductionmentioning
confidence: 99%